Delivering Compassionate Care A Mindfulness Curriculum for Interdisciplinary Healthcare Professionals - Braun, Sarah Ellen; Kinser, Patricia Anne.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook is an evidenced-based course for interdisciplinary healthcare professionals for improving resilience and reducing stress and burnout. This curriculum improves patient-centered care by providing training in compassion and attention. It is a structured skills-based manual complete with resources for full implementation and dissemination of this evidence-based course. This textbook addresses the gaps existing in other mindfulness-based interventions. It is a unique manual that can be followed in a linear fashion or can be used modularly to suit the needs of specific settings. The curriculum contains didactic content and specific examples of practices; hence, it is easily adaptable for use by groups and classes of various sizes and structure. The authors have conducted several research studies with findings to support its use to prevent and treat burnout. Results demonstrate the curriculum s feasibility and acceptability in healthcare professionals and students as well as efficacy in stress and burnout reduction with increases in dispositional mindfulness.
Foreword -- Part 1: Introduction and Overview -- Chapter 1: How to Use This Book: Teaching and Learning Mindfulness for NursesHealthcare Professionals -- Chapter 2: Evidence to Support Mindful Nurses and Healthcare Professionals -- Chapter 3: Compassion -- Chapter 4: Being Mindful in a Mindless World -- Part 2: The Curriculum -- Chapter 5: Module 1: Introduction to Mindfulness -- Chapter 6: Module 2: Mindfulness to Enhance Resilience and Handle Burnout -- Chapter 7: Module 3: Applications of Mindfulness as a NurseHealthcare Professional -- Chapter 8: Module 4: Interpersonal Mindfulness and Compassionate Patient Care -- Chapter 9: Module 5: Mindful Teams and Leadership -- Chapter 10: Module 6: Mindfulness in the Presence of Suffering -- Chapter 11: Module 7: Mindfulness and Compassion in the Face of Imperfection -- Chapter 12: Module 8: Finding Balance Through Mindful Living.
Keywords: Nursing; Patient education; Nursing; Patient Education; Burnout, Professional -- prevention & control; Empathy; Health Personnel -- psychology; Mindfulness. Self Care